Newly developed chromium-doped fiber as a saturable absorber at 1.55- and 2.0-µm regions for Q-switching pulses generation - Dutta, Debjit; Paul, Mukul Chandra; Dhar, Anirban; Das, Shyamal; Rusdi, Muhammad Farid Mohd; Latiff, Anas Abdul; Ahmad, Harith; Harun, Sulaiman Wadi (Elsevier, 2019)
We demonstrate a Q-switching operation laser at 1.55- and 2-µm region using a homemade 10 cm long of Chromium-doped fiber (CrDF) as a passive saturable absorber (SA). Erbium-doped fiber (EDF) and Thulium-doped fiber (TDF) as a gain medium cooperate in the all-fiber ring cavity configuration. CrDF was fabricated by Modified Chemical Vapour Deposition (MCVD) technique in conjunction with conventional solution doping (SD) method. The CrDF has a saturable absorption of 9% at 1.55-µm region with a saturation intensity of 22 MW/cm2. Therefore, a stable pulse train obtainable within 75–173 mW, with a repetition rate increases from 68.12 kHz to 115.9 kHz. At the maximum pump level, a shorter pulse width, maximum output power, and maximum pulse energy are 3.85 µs, 10.86 mW, and 94.1 nJ, respectively. In TDF laser cavity, the laser pulsing generates from 363 mW to 528 mW, where the repetition rate increases from 13.02 kHz to 27.62 kHz. At maximum pump power, a shorter pulse width, maximum output power, and pulse energy are obtained with 4.48 µs, 6.36 mW, and 230.27 nJ, respectively. Both pulse trains at 1.55- and 2-µm region are stable with a signal-to-noise ratio (SNR) of 71 dB and 44 dB, respectively. These findings are important to the discovery of robust passive saturable absorber development in a form of fiber which has a similar melting point to the rest of the silica fiber in the proposed cavities. Thus, it will be a kick-started to alternative form of passive SAs in developing a future high-power fiber lasers.